Perbandingan Efektifitas Pemberian Akupresur Titik Hegu dan Penggunaan Squishy Stress Ball terhadap Nyeri Persalinan Kala I - Dewi, Wistri Cendra Mulya; Purwanti, Yanik; Cholifah, Cholifah (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effectiveness of Hegu point acupressure and the use of a squishy stress ball on first stage labor pain at 'Aisyiyah Siti Fatimah Tulangan Hospital. The method used is quasi-experimental with a pre-test and post-test design approach. The results of the study showed that Hegu point acupressure and the use of squishies reduced the level of pain in the first stage of labor with results of p=0.004 (P<0.05). The conclusion of this research is that Hegu point acupressure is more effective than using squishies in reducing the level of pain in the first stage of labor. Keywords : Acupressure, First Stage Labor Pain, Squishy Stress Ball, Hegu Point.